A vintage model with endogenous growth and human capital. (15th December 2018) - Benhabib, Jess
Abstract: We develop an endogenous growth model with vintages of physical capital where human capital is endogenously produced. Under some simplifying assumptions, we can solve the model analytically and study its dynamics. We provide conditions under which a balanced growth path, in the ratio of capital to human capital, exists and is stable, with the transition dynamics exhibiting oscillatory echo effects associated with vintages.